Analisis Semantik Antologi Puisi Penyair Tanpa Bait Karya Ahmad Zayn - Dea Sholihatun Ni'mah; Devanda Rizky Novianti; Isnaini Habibatuzzahra; Muhammad Yusron Yusuf; Muhammad Nur Ashin (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study examines the semantic aspects of the poetry anthology Penyair Tanpa Bait by Ahmad Zayn, a contemporary poetic work characterized by free structure and the absence of conventional stanzas. The background of this research is rooted in the need to understand how meaning is constructed in modern poetry that departs from traditional poetic forms. The objective of this study is to describe and analyze lexical, grammatical, and referential meanings contained in the poems in order to reveal their overall semantic structure. This research employs a qualitative descriptive method with a semantic analysis approach. The data consist of words, phrases, and poetic lines selected from the anthology, which are analyzed through stages of data identification, classification, and interpretation of meaning. The findings indicate that the poems predominantly utilize lexical meanings as the foundation of interpretation, while grammatical structures and referential meanings function to strengthen symbolic and contextual meanings. The absence of stanza divisions encourages a continuous flow of meaning that emphasizes semantic cohesion rather than formal structure. The implications of this study contribute to the field of linguistic and literary studies by enriching semantic analysis of contemporary Indonesian poetry and providing a framework for interpreting non-conventional poetic texts.